LAS OBRAS DEL PEREGRINO TIBALDI EN EL ESCORIAL: UN RESUMEN ORIGINAL DEL ARTE ITALIANO DE SU TIEMPO - Scholz-Hansel, Michael (Imafronte, 1993)
Pellegrino Tibaldi carried out the main works of decoration of El Escorial (high altar, library and cloister) during the 16th century, and had to create again most of the works by Federico Zuccaro. Dealing in this paper with Tibaldi’s paintings in fresco in the library, we propose that his work mirrors the most advanced state of the ltalian art at that time. His bad reputation was only a consequence of the cultural change ocurred in Spain during the last years of the reign of Philip the Second, and of his no-reception in Europe (this was also a problem of Spanish art in general).